Frequency of Hypocalcaemia after Thyroid Surgery - Ahmed, Shabbir; Shafi, Asim; Malik, Rab Nawaz; Tahir, Umair; Ghulam, Bushra; Saleem, Farah (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: to investigate the frequency of postoperative hypocalcaemia undergoing thyroid surgery. Study design: Cross sectional study Place and duration: Study was conducted at Endocrinology department of general surgery, Bakhtawar Amin Medical and Dental College, Multan, from January 2021 to January 2022. Methodology: Study was conducted on total 115 patients who were admitted for thyroid surgery. Main variables of study were demographics, preoperative diagnosis, calcium level after surgery at 1st, 2nd and 5th day. SPSS version 23 was used for data analysis, test of significant were applied and p value ≤ 0.05 was taken as significant. Results: One hundred and fifteen patients were analyzed in our study, with mean age 38.99±4.63 years. There were 54.8% males and 45.2% females. Total thyroidectomy underwent in 46.1% patients and completion thyroidectomy underwent in 53.9% patients. Furthermore, 84.3% developed malignant and 15.7% developed benign. Hypocalcaemia developed in 9.6% patients. Among these, 54.5% malignant and 36.4% benign and only 9.1% developed permanent hypocalcaemia. On the second day of operation, 7.8% patients developed transient hypocalcaemia. While, on the fifth day of operation, 4.3% patients developed transient hypocalcaemia.2.6% patients required calcium and vitamin D supplements. Conclusion: Following thyroid surgery hypocalcaemia is a major concern that can be prevented by adopting meticulous operative technique and preserving vascularity of parathyroid glands. Continuous monitoring of serum calcium level in postoperative period and early management in cases of hypocalcaemia can significantly reduce the associated morbidity.